Effect of COVID-19 lockdown on reproductive activity in Rivers state - Gbaranor, Barinua K.; Agara, Humphrey N.; Alasia, Onisojime M.; Mube, William A.; Dumoateli, Iboroma; Ovili-Odili, Blessing Z.; Peterside, Sofiri S.; Ile, Vivian I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Reproductive activity is an important biological process that always take place between married and unmarried couples across the globe. The study was carried out to evaluate the effect of COVID-19 on reproductive activity during and post-lockdown in Rivers state. The aim of the study was to evaluate the effect of COVID-19 on reproductive activity during and post-lockdown in Rivers state. Methods: A well-structured questionnaire containing demographics and effect of COVID-19 on reproductive activity were administered to participants. Each participant had one questionnaire to fill appropriately and independently after instructions were given to them by the researchers. Results: The study revealed that 57.58% (57/99) of the participants were between the ages 16-20, 58.82% (60/102) were single and 99.03% (102/103) of the participants (women) have unprotected sexual intercourse during COVID-19 lockdown. 99.03% (102/103) the participants engaged in unprotected sex because the pharmacist’s stores were closed. The study also shows that 43.69% (103) have the urge for sex due to inactivity and 76.60% (102) of the participants got pregnant and 96.25% (77/80) of the pregnancy were not planned. 51.29% (41/80) of the participants aborted the pregnancy and 92.68% (38/41) 0f the women who got pregnant did not attend antenatal clinic. Conclusions: A total number of 103 respondents participated in the research. 76.6% of the population got pregnant during the lockdown for different reasons and most of the participants were singles and did not plan for the pregnancy.